ASSESSMENT OF NATURAL RADIOACTIVITY LEVELS IN AGRICULTURAL SOIL AND TRANSFER IN RICE IN THE KOCHANI REGION, NORTH MACEDONIA - Angeleska, Aleksandra; CHrcheva - nikolovska, Radmila; Dimitrieska Stojkovikj, Elizabeta; Angelovski, Ljupcho; Esmerov, Igor; Uzunov, Risto (Faculty of Agriculture, University of East Sarajevo, Republic of Srpska, Bosnia and Herzegovina..., 2025)
Soil can transfer radionuclides to plants which are subsequently consumed by humans. Sometimes their levels are so high that they are a concern for human health. Rice has an important share in the Macedonian diet, especially in the Kochani region, which is famous for its rice fields. Therefore, the main goal of this study was to measure the natural radioactivity in agricultural soil and rice crops in the Kochani region and to study the interaction between soil and rice by calculating the transfer factor (TF). The activity concentrations of 226Ra, 232Th and 40K were determined by using gamma spectrometry, i.e. a high purity germanium (HPGe) gamma-ray spectrometer. In agricultural soils, the mean activity concentrations of 226Ra, 232Th and 40K were 33.72 Bq kg-1, 37.62 Bq kg-1 and 152.90 Bq kg-1, while the mean activity concentrations of rice were 1.99 Bq kg-1, 2.51 Bq kg-1and 49.44 Bq kg-1, respectively. The world’s mean soil values of 226Ra, 232Th and 40K are 35, 30 and 400 Bq kg-1, respectively, hence these obtained values are lower compared to those obtained from research. This may be due to improved agricultural practices in the country and the geology of the area itself. However, we found that the radioisotopes have a heterogeneous distribution which must be caused by the nature and soil types in the area for which this study was conducted. However, the radioisotopes showed a heterogeneous distribution, likely influenced by the nature and soil types in the region. The mean transfer factors (TF) were very low for all samples, indicating a slow transport of these radionuclides to the rice grains. The results confirm that rice grown in these areas is safe for consumption. Further research on the TF across different rice varieties and geographical areas would allow for the development of predictive models for potential radiation exposure from rice consumption and help identify locations requiring additional monitoring. All mean transfer factors (TF) for the samples were very low, implying a very slow transport of these radionuclides to the rice grains. The obtained results make rice grown in these areas safe for consumption. By studying the TF among different rice varieties and geographical areas, researchers will be able to develop models to predict possible radiation exposure from rice consumption and locate activities or areas that require additional attention.
Keywords: HPGe Detector, Natural radiation, Soil, Rice, Transfer factor (TF)